INVЕSTIGАTIОN ОF THЕ KINЕTIСS ОF Сr(VI) IОN SОRPTIОN FRОM АRTIFIСIАL SОLUTIОNS ОN INDUSTRIАL АNIОNITЕ (Scientific journal of the Fergana State University, 2024)
Removing Cr (VI) ions in industrial wastewater is an urgent problem. Cr (VI) ions are very toxic, they harm the environment and human health. The kinetics of sorption of Cr (VI) ions from artificial solutions to AN-31 anionite, which is used on an industrial scale, was studied. The evaluation of sorption kinetics and adsorption mechanism was based on pseudo-first and pseudo-second-order kinetic models. The sorption kinetics of Cr(VI) ions to AN-31 anionite was a pseudo-second-order model, and the adsorption capacity was 5.60 mg-eq/g.